Estudo para implantação de turbina de fluxo cruzado tipo Michell-Banki na micro central hidrelétrica de Roncador - Uno, Victor Hugo Akio Benassi (2012)
Federal Technological University of Paraná (UTFPR) and Bocaiúva do Sul’s city hall in partnership, are reactivating the Micro Hydroelectric Power Plant of Roncador for electricity generation and use as a teaching laboratory complementing the theoretical at the University. The work consists primarily in the study for installation of the turbine cross-flow, type Michell-Banki, in the Micro Hydroelectric Power Plant of Roncador. This turbine is defined as an action turbine and can be installed in falls from 1 to 200 m of height and flow of 0,025 to 13 m³/s , it can reach diameters of rotors near 1,0 m with a width of 3,0 m and develop power up to 2000 m, with yields of up to 90%. The second part of the work is the creation of a penstock with multiple outlets for installation of several turbines and can therefore carry out practical studies and comparative.